Sustainable Tourism Development Analysis in Blimbingsari Tourism Village, Banyuwangi, East Java - Kanom, Kanom; Rusmawan, Putu Ngurah; Nurhalimah, Nurhalimah (Sebatik, 2025)
This study aims to analyze sustainable tourism development strategies in Blimbingsari Tourism Village, Banyuwangi, East Java. The method used is qualitative descriptive with SWOT analysis to identify strengths, weaknesses, opportunities, and threats in tourism village management. Data was obtained through literature studies, government agency reports, and scientific publications from the last five years (2020–2025). The results of the study show that Blimbingsari Village has great potential through beach tourism, grilled fish cuisine, and community-based management. However, the challenges faced include limited institutional capacity, supporting infrastructure, and the risk of environmental degradation due to an increase in the number of tourists. The main strategies recommended include increasing community institutional capacity, diversifying tourism products, and implementing ecotourism principles and sustainable digital promotion. This study emphasizes the importance of collaboration between the community, government, and tourism stakeholders to realize adaptive, inclusive, and sustainable tourism development in Blimbingsari Tourism Village.